FRI0330 MALIGNANCIES IN SYSTEMIC SCLEROSIS PATIENTSWITH ANTI-PM/SCL ANTIBODIES: AN EUSTAR CASE- CONTROL STUDY. (June 2019) - Lazzaroni, Maria Grazia; Zingarelli, Stefania; Vries-Bouwstra, Jeska de; Hachulla, Eric; Zanatta, Elisabetta; Barsotti, Simone; Truchetet, Marie-Elise; Luca, Giacomo De; Smith, Vanessa; Langhe, Ellen De; Hesselstrand, Roger; Ingegnoli, Francesca; et al.
Abstract : Background: The main clinical associations of anti-PM/Scl in Systemic Sclerosis (SSc) include calcinosis, joint and muscle involvement, interstitial lung disease (ILD), and, possibly, scleroderma renal crisis (1, 2). A possible association of anti-PM/Scl with cancer was reported in single-centre SSc series (2, 3), but was never analysed in large multicentre studies. Moreover, the characteristics of malignancies, in particular their temporal association with the onset of SSc, were not explored. Objectives: To evaluate the association of anti-PM/Scl with malignancies in a large, international, multicentre cohort. Methods: 16 EUSTAR centres provided data on anti-PM/Scl+ SSc patients in their cohorts (cases), and on anti-PM/Scl-negative controls, matched for sex, age at onset (±5 years), cutaneous subset, and disease duration (±24 months). Only SSc patients with age >16 years at disease onset were included in this analysis. Anti-RNA Polymerase3+ patients were not included in controls, given the known association with synchronous cancer. Malignancies diagnosed between 2 years before and after the onset of SSc were defined as "synchronous to the onset of SSc". Results: 123 anti-PM/Scl+ SSc patients and 160 matched anti-PM-Scl- controls (28% anti-Topoisomerase I, 40% anti-centromere, 32% others) were compared (Table 1 ): anti-Pm/Scl+ patients had a higher prevalence of myositis (p<0.0001) and ILD (p<0.0001), and a lower prevalence of oesophageal symptoms (p<0.0001). The frequency of malignancies was not significantly different between the 2 groups (14/120 (12%) vs. 9/155 (6%), p:0.12). Only 7 malignancies synchronous to SSc onset were identified: 4 among anti-PM/Scl+ cases and 3 among controls (3 breast cancers; 3 other solid tumours; 1 multiple myeloma). Mean age at SSc onset was significantly higher in patients with synchronous malignancies compared to those without (64.9±7.2 vs. 48.4±14.5 years; p:0.003), irrespective of the anti-PM/Scl status. Conclusion: in this EUSTAR multicentre case control-study, the association of anti-Pm/Scl with malignancies in SSc patients could not be confirmed. Patients with older age at SSc onset seems to be at higher risk for synchronous malignancies, regardless the autoantibody status. References: [1] Lazzaroni MG, et al. Ann Rheum Dis2018; 77:(Suppl 2), 421-422. [2] Bruni C, et al. Rheumatology (Oxford). 2017;56:317-8. [3] Bernal-Bello D, et al. Autoimmun Rev2017;16:461-8. Acknowledgement: Authors would like to thank GILS (Gruppo Italiano Lotta Sclerodermia) for the grant to support this project Disclosure of Interests: Maria Grazia Lazzaroni: None declared, Stefania Zingarelli: None declared, Jeska de Vries-Bouwstra: None declared, Eric Hachulla Consultant for: Received consulting fees or other remuneration from Actelion, GSK, Pfizer, and Bayer, Elisabetta Zanatta: None declared, Simone Barsotti: None declared, Marie-Elise Truchetet: None declared, Giacomo De Luca Speakers bureau: Pfeizer, Sobi, Vanessa Smith: None declared, Ellen De Langhe: None declared, Roger Hesselstrand: None declared, Francesca Ingegnoli: None declared, Cristian Caimmi: None declared, Silvia Bellando Randone: None declared, Enrico Colombo: None declared, Angela Ceribelli: None declared, Franco Franceschini: None declared, Yannick Allanore Grant/research support from: Inventiva, F Hoffman La-Roche, Sanofi, BMS, Pfizer, Consultant for: Actelion, Bayer, BMS, Boehringer, Roche, Sanofi, Paolo Airò: None declared